Soft Interventions: Collaborative Agencies Between Artists and Photography Editing Software - Jane Vuorinen (Finland, 2022)
Recently there has been a growing number of artists working between photography and digital art, creating artworks in which the signs of digital operations have been left visible. I focus on three contemporary artists who use photography as a starting point in a process in which the work done in the digital environment of photography editing software is an equally important creative phase as the initial taking of the photograph: Andrey Bogush, Liina Aalto-Setälä and Aaron Hegert. Starting from a reconfiguration of single authorship, I examine what kinds of subjectivities and agencies these works and practices produce, and how producing and encountering the works through screens affect our understanding of them. I stress the activity and agency of the editing software as an integral part of the artistic process. The three main areas of inquiry are originality, collaborative models of production, and authenticity. In the analysis, automatization becomes a generative engine, and the editing software a site for artistic creation, rather than a mere post-production tool.